2004
DOI: 10.1002/ejoc.200400010
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition of Benzonitrile Oxide to Acetonitrile, Propyne and Propene − A Comparative Theoretical Study of the Reaction Mechanism and Regioselectivity

Abstract: Quantum chemical calculations (MP2/6-31G* and B3LYP/6-31G*) were used to compare the reactivity, regioselectivity and orbital involvement of the reaction of benzonitrile oxide with the dipolarophiles acetonitrile, propyne and propene. All reactions are thermodynamically favoured. The product stability decreases in an order propyne Ͼ acetonitrile Ͼ propene, and reflects the degree of aromatic stabilisation of the product. The activation barriers depend strongly on the computational method used and decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…[4] This method is fairly general and complements classical condensation methods because of its greater functional group compatibility and the use of milder The 13DC reactions of nitrile oxides have also been theoretically studied. [5][6][7][8] The regioselectivity of the 13DC reactions of benzonitrile N-oxides (NBOs) with ED alkynes and alkenes has been studied by Hu and Houk. [7] The transition-state structures (TSs) for the reactions of fulminic acid (1) and mesitonitrile oxide (2) and the ED methyl propiolate (3) and cyanoacetylene (4) have been studied at the B3LYP/6-31G* level of theory (see Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] This method is fairly general and complements classical condensation methods because of its greater functional group compatibility and the use of milder The 13DC reactions of nitrile oxides have also been theoretically studied. [5][6][7][8] The regioselectivity of the 13DC reactions of benzonitrile N-oxides (NBOs) with ED alkynes and alkenes has been studied by Hu and Houk. [7] The transition-state structures (TSs) for the reactions of fulminic acid (1) and mesitonitrile oxide (2) and the ED methyl propiolate (3) and cyanoacetylene (4) have been studied at the B3LYP/6-31G* level of theory (see Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wagner and co-workers [8] studied the 13DC reactions of benzonitrile oxide (9) with propene (10) and propyne (11) at the same level of theory (see Scheme 3). Note that the methyl group nucleophilically activates these π systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Diels-Alder reactions, which are known to be under kinetic control, 46,[78][79][80] it is not clear if 13DC reactions have kinetic control or thermodynamic control. 80 However, experimental 81 and theoretical 24,82 studies involving nitrile oxides point to mechanisms controlled in a kinetic way. Furthermore, it has also been reported that a preference for β face attack, which is more sterically hindered due to torsional factors (such as a preference for staggered conformations and for the concave face of the envelope conformation in cyclopentene rings) 83 has more relevance than steric factors and governs stereoselectivity in several cases.…”
Section: 76mentioning
confidence: 99%
“…18 From the pioneering work of Huisgen,19,20 who postulated the concerted reaction mechanism of cycloaddition reactions, this kind of reaction has been widely studied, both theoretically and experimentally. [21][22][23][24][25][26][27][28][29][30] The control of regioselectivity of 13DC has been explained by frontier molecular orbital (FMO) analysis. 2,3 In this treatment, the nucleophilicity and electrophilicity of the species are based on HOMO and LUMO energies and orbital coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation